Linking solar-induced chlorophyll fluorescence to biogenic volatile organic compound emissions in low Arctic tundra: A field spectroscopy approach - Federico Grillini; Simon Nyboe Laursen; Amy Smart; Peiyan Wang; Shunan Feng; Juliane Bendig; Andreas Westergaard-Nielsen (Remote Sensing of Environment, 2026)

Translating community perceptions and concerns into planning: climate change adaptation in Hooper Bay, Alaska - Joseph T. Molina; Agatha A. Napoleon; Estelle Angutekaraq Thomson; Colleen Timmer; Andre Simon; Agulria Smart; Billy Tinker-Smith; Nicole Schmitt; Chelsey Cook (Regional Environmental Change, 2026)

Characterising the supply- and demand-sides of the net-zero transition to inform sectoral decarbonisation policy - Andrea Vecchi; Yimin Zhang; Dominic Davis; Ryan Jones; Simon Smart; Chris Greig; Michael Brear (Energy Policy, 2026)

Multi-source remote sensing of insect defoliation events in Abisko from point to regional scales - Shunan Feng; Simon Nyboe Laursen; Amy Smart; Katrine Stadsholt Sørensen; Monika Lund; Federico Grillini; Jolanta Rieksta; Yi Jiao; Riikka Rinnan; Andreas Westergaard-Nielsen (Agricultural and Forest Meteorology, 2026)

Forest Topsoil Organic Carbon Declines Under Ash Dieback - Fiona M. Seaton; David A. Robinson; Claire M. Wood; Clare M. H. Benskin; Rebecca L. Rowe; Karen Hornigold; Keith J. Kirby; Chris Nichols; Simon M. Smart (Global Change Biology, 2025)
Tree diseases are increasingly affecting woodland ecosystems across the world. However, the impact of these diseases upon the soil, and in particular soil carbon, is still poorly understood. Here we present the results of a field survey of ~100 woodlands across Great Britain measured in 1971, 2001 and 2022 and evaluate the fifty‐year trend in topsoil (0–15 cm) carbon based upon measurements of soil organic matter (SOM) and the impact of Hymenoscyphus fraxineus (ash dieback). To better represent the full SOM distribution, including the extremely high SOM measurements, we adopt a Beta mixture modelling approach within a Bayesian framework. Across all woodlands, comprising ~1,500 plots per survey, average SOM remained constant across the fifty‐year time series. However, the 311 plots with ash dieback had lower SOM in the most recent survey compared to the 328 plots with ash trees present but no dieback recorded, due to a slight decline in SOM under ash dieback. This resulted in plots with ash dieback having a modelled mean SOM of 12.2% compared to 13.4% in plots without ash dieback, a difference of 1.23 percentage points (95% CI 0.25–2.21). Ash dieback was more likely to be recorded in plots that had higher soil pH pre‐ash dieback invasion, but the decline in SOM under ash dieback was not explained by changes in soil pH or changes in the ground flora composition. Converting our results to soil C and extrapolating for broadleaved woodland across the entirety of Great Britain, the total amount of topsoil carbon lost to date due to ash dieback could be 6 MtCO 2 (± 4 s.d.). Our results show the importance of understanding the impacts of tree disease when considering current and future woodland carbon dynamics.

Elevated CO 2 interacts with nutrient inputs to restructure plant communities in phosphorus‐limited grasslands - Christopher R. Taylor; Luke C. England; J. Ben Keane; Jessica A. C. Davies; Jonathan R. Leake; Iain P. Hartley; Simon M. Smart; Victoria Janes‐Bassett; Gareth K. Phoenix (Global Change Biology, 2024)
Globally pervasive increases in atmospheric CO 2 and nitrogen (N) deposition could have substantial effects on plant communities, either directly or mediated by their interactions with soil nutrient limitation. While the direct consequences of N enrichment on plant communities are well documented, potential interactions with rising CO 2 and globally widespread phosphorus (P) limitation remain poorly understood. We investigated the consequences of simultaneous elevated CO 2 (eCO 2 ) and N and P additions on grassland biodiversity, community and functional composition in P‐limited grasslands. We exposed soil‐turf monoliths from limestone and acidic grasslands that have received >25 years of N additions (3.5 and 14 g m −2 year −1 ) and 11 (limestone) or 25 (acidic) years of P additions (3.5 g m −2 year −1 ) to eCO 2 (600 ppm) for 3 years. Across both grasslands, eCO 2 , N and P additions significantly changed community composition. Limestone communities were more responsive to eCO 2 and saw significant functional shifts resulting from eCO 2 –nutrient interactions. Here, legume cover tripled in response to combined eCO 2 and P additions, and combined eCO 2 and N treatments shifted functional dominance from grasses to sedges. We suggest that eCO 2 may disproportionately benefit P acquisition by sedges by subsidising the carbon cost of locally intense root exudation at the expense of co‐occurring grasses. In contrast, the functional composition of the acidic grassland was insensitive to eCO 2 and its interactions with nutrient additions. Greater diversity of P‐acquisition strategies in the limestone grassland, combined with a more functionally even and diverse community, may contribute to the stronger responses compared to the acidic grassland. Our work suggests we may see large changes in the composition and biodiversity of P‐limited grasslands in response to eCO 2 and its interactions with nutrient loading, particularly where these contain a high diversity of P‐acquisition strategies or developmentally young soils with sufficient bioavailable mineral P.

Combining multiple investigative approaches to unravel functional responses to global change in the understorey of temperate forests - Dries Landuyt; Michael P. Perring; Haben Blondeel; Emiel De Lombaerde; Leen Depauw; Eline Lorer; Sybryn L. Maes; Lander Baeten; Laurent Bergès; Markus Bernhardt‐Römermann; Guntis Brūmelis; Jörg Brunet; et al. (Global Change Biology, 2024)
Plant communities are being exposed to changing environmental conditions all around the globe, leading to alterations in plant diversity, community composition, and ecosystem functioning. For herbaceous understorey communities in temperate forests, responses to global change are postulated to be complex, due to the presence of a tree layer that modulates understorey responses to external pressures such as climate change and changes in atmospheric nitrogen deposition rates. Multiple investigative approaches have been put forward as tools to detect, quantify and predict understorey responses to these global‐change drivers, including, among others, distributed resurvey studies and manipulative experiments. These investigative approaches are generally designed and reported upon in isolation, while integration across investigative approaches is rarely considered. In this study, we integrate three investigative approaches (two complementary resurvey approaches and one experimental approach) to investigate how climate warming and changes in nitrogen deposition affect the functional composition of the understorey and how functional responses in the understorey are modulated by canopy disturbance, that is, changes in overstorey canopy openness over time. Our resurvey data reveal that most changes in understorey functional characteristics represent responses to changes in canopy openness with shifts in macroclimate temperature and aerial nitrogen deposition playing secondary roles. Contrary to expectations, we found little evidence that these drivers interact. In addition, experimental findings deviated from the observational findings, suggesting that the forces driving understorey change at the regional scale differ from those driving change at the forest floor (i.e., the experimental treatments). Our study demonstrates that different approaches need to be integrated to acquire a full picture of how understorey communities respond to global change.

An adaptable integrated modelling platform to support rapidly evolving agricultural and environmental policy - Paula A. Harrison; Kate Beauchamp; Joe Cooper; Ian Dickie; Alice Fitch; Richard Gooday; Michael Hollaway; Ian P. Holman; Merryn Hunt; Laurence Jones; Thomas Mondain-Monval; Daniel Sandars; et al. (Environmental Modelling & Software, 2023)

Resilience of ecosystem service delivery in grasslands in response to single and compound extreme weather events - Rosalind J. Dodd; David R. Chadwick; Paul W. Hill; Felicity Hayes; Antonio R. Sánchez-Rodríguez; Dylan Gwynn-Jones; Simon M. Smart; Davey L. Jones (Science of The Total Environment, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Zones of influence for soil organic matter dynamics: A conceptual framework for data and models - Claudia Cagnarini; Eleanor Blyth; Bridget A. Emmett; Chris D. Evans; Robert I. Griffiths; Aidan Keith; Laurence Jones; Inma Lebron; Niall P. McNamara; Jeremy Puissant; Sabine Reinsch; David A. Robinson; et al. (Global Change Biology, 2019)
Soil organic matter (SOM) is an indicator of sustainable land management as stated in the global indicator framework of the United Nations Sustainable Development Goals (SDG Indicator 15.3.1). Improved forecasting of future changes in SOM is needed to support the development of more sustainable land management under a changing climate. Current models fail to reproduce historical trends in SOM both within and during transition between ecosystems. More realistic spatio‐temporal SOM dynamics require inclusion of the recent paradigm shift from SOM recalcitrance as an ‘intrinsic property’ to SOM persistence as an ‘ecosystem interaction’. We present a soil profile, or pedon‐explicit, ecosystem‐scale framework for data and models of SOM distribution and dynamics which can better represent land use transitions. Ecosystem‐scale drivers are integrated with pedon‐scale processes in two zones of influence. In the upper vegetation zone, SOM is affected primarily by plant inputs (above‐ and belowground), climate, microbial activity and physical aggregation and is prone to destabilization. In the lower mineral matrix zone, SOM inputs from the vegetation zone are controlled primarily by mineral phase and chemical interactions, resulting in more favourable conditions for SOM persistence. Vegetation zone boundary conditions vary spatially at landscape scales (vegetation cover) and temporally at decadal scales (climate). Mineral matrix zone boundary conditions vary spatially at landscape scales (geology, topography) but change only slowly. The thicknesses of the two zones and their transport connectivity are dynamic and affected by plant cover, land use practices, climate and feedbacks from current SOM stock in each layer. Using this framework, we identify several areas where greater knowledge is needed to advance the emerging paradigm of SOM dynamics—improved representation of plant‐derived carbon inputs, contributions of soil biota to SOM storage and effect of dynamic soil structure on SOM storage—and how this can be combined with robust and efficient soil monitoring.

Model‐based hypervolumes for complex ecological data - Susan G. Jarvis; Peter A. Henrys; Aidan M. Keith; Ellie Mackay; Susan E. Ward; Simon M. Smart (Ecology, 2019)
Developing a holistic understanding of the ecosystem impacts of global change requires methods that can quantify the interactions among multiple response variables. One approach is to generate high dimensional spaces, or hypervolumes, to answer ecological questions in a multivariate context. A range of statistical methods has been applied to construct hypervolumes but have not yet been applied in the context of ecological data sets with spatial or temporal structure, for example, where the data are nested or demonstrate temporal autocorrelation. We outline an approach to account for data structure in quantifying hypervolumes based on the multivariate normal distribution by including random effects. Using simulated data, we show that failing to account for structure in data can lead to biased estimates of hypervolume properties in certain contexts. We then illustrate the utility of these “model‐based hypervolumes” in providing new insights into a case study of afforestation effects on ecosystem properties where the data has a nested structure. We demonstrate that the model‐based generalization allows hypervolumes to be applied to a wide range of ecological data sets and questions.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Clarifying the key biodiversity areas partnership and programme - Simon N. Stuart; Thomas M. Brooks; Stuart H. M. Butchart; Wendy Elliott; Melanie Heath; Dieter Hoffmann; Leslie Honey; Irina Kostadinova; Penny Langhammer; Olivier Langrand; Susan Lieberman; Daniel Marnewick; et al. (Biodiversity and Conservation, 2018)

Resistin and NGAL are associated with inflammatory response, endothelial activation and clinical outcomes in sepsis - Stephen P. J. Macdonald; Erika Bosio; Claire Neil; Glenn Arendts; Sally Burrows; Lisa Smart; Simon G. A. Brown; Daniel M. Fatovich (Inflammation Research, 2017)

Legacy effects of grassland management on soil carbon to depth - Susan E. Ward; Simon M. Smart; Helen Quirk; Jerry R. B. Tallowin; Simon R. Mortimer; Robert S. Shiel; Andrew Wilby; Richard D. Bardgett (Global Change Biology, 2016)
The importance of managing land to optimize carbon sequestration for climate change mitigation is widely recognized, with grasslands being identified as having the potential to sequester additional carbon. However, most soil carbon inventories only consider surface soils, and most large‐scale surveys group ecosystems into broad habitats without considering management intensity. Consequently, little is known about the quantity of deep soil carbon and its sensitivity to management. From a nationwide survey of grassland soils to 1 m depth, we show that carbon in grassland soils is vulnerable to management and that these management effects can be detected to considerable depth down the soil profile, albeit at decreasing significance with depth. Carbon concentrations in soil decreased as management intensity increased, but greatest soil carbon stocks (accounting for bulk density differences), were at intermediate levels of management. Our study also highlights the considerable amounts of carbon in subsurface soil below 30 cm, which is missed by standard carbon inventories. We estimate grassland soil carbon in Great Britain to be 2097 Tg C to a depth of 1 m, with ~60% of this carbon being below 30 cm. Total stocks of soil carbon (t ha −1 ) to 1 m depth were 10.7% greater at intermediate relative to intensive management, which equates to 10.1 t ha −1 in surface soils (0–30 cm), and 13.7 t ha −1 in soils from 30 to 100 cm depth. Our findings highlight the existence of substantial carbon stocks at depth in grassland soils that are sensitive to management. This is of high relevance globally, given the extent of land cover and large stocks of carbon held in temperate managed grasslands. Our findings have implications for the future management of grasslands for carbon storage and climate mitigation, and for global carbon models which do not currently account for changes in soil carbon to depth with management.

Empirical realised niche models for British coastal plant species - Susan G. Jarvis; Edwin C. Rowe; Peter A. Henrys; Simon M. Smart; Laurence Jones; Angus Garbutt (Journal of Coastal Conservation, 2016)

Inertia in an ombrotrophic bog ecosystem in response to 9 years' realistic perturbation by wet deposition of nitrogen, separated by form - Lucy J. Sheppard; Ian D. Leith; Toshie Mizunuma; Sarah Leeson; Sanna Kivimaki; J. Neil Cape; Netty van Dijk; David Leaver; Mark A. Sutton; David Fowler; Leon J.L. Van den Berg; Alan Crossley; et al. (Global Change Biology, 2014)
Wet deposition of nitrogen (N) occurs in oxidized (nitrate) and reduced (ammonium) forms. Whether one form drives vegetation change more than the other is widely debated, as field evidence has been lacking. We are manipulating N form in wet deposition to an ombrotrophic bog, Whim (Scottish Borders), and here report nine years of results. Ammonium and nitrate were provided in rainwater spray as NH 4 Cl or NaNO 3 at 8, 24 or 56 kg N ha −1 yr −1 , plus a rainwater only control, via an automated system coupled to site meteorology. Detrimental N effects were observed in sensitive nonvascular plant species, with higher cumulative N loads leading to more damage at lower annual doses. Cover responses to N addition, both in relation to form and dose, were species specific and mostly dependent on N dose. Some species were generally indifferent to N form and dose, while others were dose sensitive. Calluna vulgaris showed a preference for higher N doses as ammonium N and Hypnum jutlandicum for nitrate N. However, after 9 years, the magnitude of change from wet deposited N on overall species cover is small, indicating only a slow decline in key species. Nitrogen treatment effects on soil N availability were likewise small and rarely correlated with species cover. Ammonium caused most N accumulation and damage to sensitive species at lower N loads, but toxic effects also occurred with nitrate. However, because different species respond differently to N form, setting of ecosystem level critical loads by N form is challenging. We recommend implementing the lowest value of the critical load range where communities include sensitive nonvascular plants and where ammonium dominates wet deposition chemistry. In the context of parallel assessment at the same site, N treatments for wet deposition showed overall much smaller effects than corresponding inputs of dry deposition as ammonia.

Reply to Comment: Holocene palaeoceanographic changes in Barrow Strait, Canadian Arctic: foraminiferal evidence. T. R. Gregory, C. W. Smart, M. B. Hart, G. Massé, L. L. Vare and S. T. Belt (2010). Journal of Quaternary Science 25 : 903–910 - Thomas R. Gregory; Christopher W. Smart; Malcolm B. Hart; Guillaume Massé; Lindsay L. Vare; Simon T. Belt (Journal of Quaternary Science, 2010)

Holocene palaeoceanographic changes in Barrow Strait, Canadian Arctic: foraminiferal evidence - Thomas R. Gregory; Christopher W. Smart; Malcolm B. Hart; Guillaume Massé; Lindsay L. Vare; Simon T. Belt (Journal of Quaternary Science, 2010)
Holocene changes in the benthic and planktic foraminiferal fauna (>63 µm) from a marine sediment core (ARC‐3 Canadian Arctic Archipelago, 74° 16.050′ N, 91° 06.380′ W, water depth 347 m) show that significant environmental and palaeoceanographic variations occurred during the last 10 ka. Foraminiferal assemblages are restricted to the ca. 4.5–10 ka interval as younger samples are mostly barren of foraminifera due to intense carbonate dissolution after ca. 4.5 ka. Foraminiferal assemblages in the ca. 4.5–10 ka interval are dominated by the benthic species Islandiella helenae and Cassidulina reniforme (57% of total), with Elphidium clavatum , Cibicides lobatulus and Buccella frigida also being common in this interval. The dominance of these species indicates a seasonal sea ice regime which is consistent with the occurrence of the sea ice diatom‐derived organic geochemical biomarker IP 25 throughout the core. The abundances of C. reniforme and E. clavatum decline upcore; consistent with more frequent mixing of the Barrow Strait water column during the early Holocene. It is likely that the influence of CO 2 ‐rich Arctic surface water masses have caused an increase in bottom water corrosivity after ca. 8.5 ka, and dissolution has been further enhanced by sea ice‐related processes after ca. 6 ka, concomitant with increased IP 25 fluxes. Dissolution is strongest when IP 25 fluxes are highest, suggesting a link between the sea ice and benthic systems. Copyright © 2010 John Wiley & Sons, Ltd.

Nitrogen deposition causes widespread loss of species richness in British habitats - LINDSAY C. MASKELL; SIMON M. SMART; JAMES M. BULLOCK; KEN THOMPSON; CARLY J. STEVENS (Global Change Biology, 2010)
We use national scale data to test the hypothesis that nitrogen (N) deposition is strongly negatively correlated with plant species richness in a wide range of ecosystem types. Vegetation plots from a national ecological surveillance programme were drawn from heathland, acid, calcareous and mesotrophic grassland habitats. Mean species number and mean plant traits were calculated for each plot and related to atmospheric N deposition. There was a significant reduction in species richness with N deposition in acid grassland and heathland even after fitting covarying factors. In acid grassland and heathland, evidence from trait changes suggested that acidification rather than increased fertility was responsible for species loss. In contrast, calcareous grassland showed evidence of eutrophication in response to increasing N deposition. Loss of species richness from chronic N deposition is apparent in infertile grasslands and heathland. Mechanisms associated with loss of species richness differ between habitats so mitigation of N deposition should be targeted to habitat type.

Late Quaternary upwelling off tropical NW Africa: new micropalaeontological evidence from ODP Hole 658C - Simon K. Haslett; Christopher W. Smart (Journal of Quaternary Science, 2006)
Planktonic foraminifera and radiolaria have been analysed in a Late Quaternary (40–0 ka) sediment sequence from Ocean Drilling Program (ODP) Hole 658C located under a coastal upwelling system near Cap Blanc, offshore northwest Africa, in order to document the palaeoceanographic history of the area. Temporal variations in species abundance and faunal assemblage analysis reveal a tripartite phased sequence of palaeoceanographic change through the Late Quaternary. Phase 1 spans 40–14.5 ka and is characterised by moderate upwelling, but Heinrich event 2 is distinguished as a brief episode of strengthened upwelling. Phase 2 begins with a change in a number of variables at ca. 14.5 ka and extends to ca. 5.5 ka. This phase is characterised by a general strengthening of upwelling, but may be subdivided into three minor phases including (a) the recognition of the Younger Dryas, marked by a temporary reduction in upwelling strength, followed by (b) an intensification of upwelling, and (c) upwelling and high productivity between 8 and 5.5 ka. This phase of upwelling corresponds with maximum Holocene cooling, possibly triggered by the collapse of the Laurentide ice sheet. Phase 3 extends from 5.5 to 0 ka and is characterised by weak upwelling and significant calcite dissolution. These phases are related to climatic events, particularly the African Humid Period (AHP), which is coincident with Phase 2. The AHP is characterised by increased precipitation, linked to an intensification of the African monsoon that enhances North East Trade Wind‐driven coastal upwelling and is associated with the expansion of continental vegetation across North Africa. Copyright © 2006 John Wiley & Sons, Ltd.

Locating eutrophication effects across British vegetation between 1990 and 1998 - Simon M. Smart; Joanne C. Robertson; Eleanor J. Shield; Helena M. Van De Poll (Global Change Biology, 2003)
Large‐scale ecological surveillance data were analysed to determine the locations of apparent eutrophication effects across common British vegetation types between 1990 and 1998. Plant species composition was recorded from a total of 9514 fixed plots located in a stratified, random sample of 501 1 km squares across Britain. Changes in plant species composition along a gradient of substrate fertility were inferred from statistical tests of change in mean Ellenberg fertility value calculated for each fixed plot. Plots were grouped by eight vegetation types, five landscape features (hedges, road verges, watercourse banks, small biotopes, larger units in fields and unenclosed land) and six environmental zones. Tests of change in mean Ellenberg value were carried out on all combinations of these strata. Decision tree modelling was used to identify groups of test outcomes sharing the same direction of change and where each group was defined by a minimum number of strata. Post hoc power analysis was used to select statistically non‐significant test outcomes that could be used to infer stability in the sampled sub‐population. Out of a total of 142 tests of change in fertility value, 67% were increases, 8% were reductions and 25% indicated stability. The best overall predictor of increases in fertility value, and therefore of shifts in favour of plants suited to higher substrate fertility, was vegetation type. Irrespective of landscape feature and environmental zone, increased means were associated with infertile grasslands, moorland, upland woodlands and heath/bog. Already highly fertile grasslands and woodland assemblages in lowland Britain remained largely stable. The small number of decreasing test outcomes were associated with arable land in Scotland, Wales and western England. These patterns of change are hypothesized to reflect pervasive land‐use drivers combined with the inherent responsiveness of the vegetation.

Ecological assessment of vegetation from a nature reserve using regional reference data and indicator scores - Simon M. Smart (Biodiversity and Conservation, 2000)